The increasing of phosphorus availability and corn growth (Zea mays l.) With the application of phosphate solubilizing microbes and some sources of organic materials on andisol. (May 2019) - Masdariah,; Sembiring, M; Mukhlis,; Rosneli,
Abstract: Andisol is a soil that develops from volcanic ash material, dominated by amorphous aluminium silicate and Al-humus complex. This research was carried out at the Greenhouse and Laboratory of Soil Biology, Faculty of Agriculture, University of Sumatera Utara, Medan. This research used a randomized block design with 2 treatment factors and 3 replications. The first factor was Phosphate Solubilizing Microbial (PSM), namely: without application (M0 ), 5 g of Mycorrhiza (M1 ), 5 gr of Talaromyces pinophilus Fungi (M2 ), 5 g of Burkholderia cepacia Bacteria (M3 ). The second factor was organic matter, namely: without application (K0 ), 180 g of cow dung (K1 ), 180 g of chicken manure (K2 ) and 180 g of OPEFB (Oil Palm Empty Fruit Bunch) compost (K3 ). The research results showed that the administration of phosphate solubilizing microbes and several sources of organic matter could increase the soil pH by 0.61-29.12%, P-available by 1.46-112.64%, plant height by 5.41-19.25% and canopy dry weight by 11.34-65.57%. In general, the best treatment was the application of Mycorrhiza with OPEFB (Oil Palm Empty Fruit Bunch) compost.